KAJIAN POTENSI PENGEMBANGAN EKOWISATA DI SUAKA MARGASATWA SERMO KABUPATEN KULONPROGO YOGYAKARTA - , Sulistyo Widodo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The development of wildlife areas into ecotourism requires careful planning because at the wildlife area, tourism is one of the management goals that allowed if the condition of the region is possible to be a tourist area. Therefore, it is very important to know the potential of wildlife area and the factors that can influence it, so that in its development efforts does not provide opportunities for the occurrence of the things which can damage the preservation and ecosystem balance in the area. There were various methods used in this study, i.e. data collection of flora use transect method with a systematic sampling for the determination of plots (sampling intentity is 1%), data retrieval fauna use line transect method with a recording take from the List of MacKinnon, landscape data was taken by the potential for visual observation with reference to the parameters of Berau of Land Management (1986) and retrieval of data community and perceptions of tourists use questionnaires by random sampling (sampling intentity is 10%) and interaction between the nearest destination take the gravity model. The results show that the quality of flora diversity is very good (criteria by Fandeli (1992)) as many as 48 species of flora. The quality of fauna diversity is also very good (criteria by Fandeli (1992)), as many as 44 species of fauna. The potential landscape has visual A quality or very good. Perception of tourists show that tourists agree with the development of the Suaka Margasatwa Sermo as an object of ecotourism. In addition, the surrounding community also supports ecotourism activities which expected to conserve the area and be able to improve their welfare. The opportunity of tourists movement from nearest destination show that there are movements of tourists as many as 738 people per year from Borobudur Temple and Glagah Beach. Thus, overall Suaka Margasatwa Sermo is very potential to be developed as ecotourism object.